A study on the design and performance of ModuleRaft wave energy converter. (January 2021) - Tongphong, Watchara; Kim, Byung-Ha; Kim, In-Cheol; Lee, Young-Ho
Abstract: This paper presents a novel wave energy converter (WEC), referred to as the ModuleRaft WEC. The WEC consists of a floating modular flap and four rafts hinged at the main floating structure. ModuleRaft WEC is unique due to its ability to convert both wave potential energy and wave kinetic energy by utilizing the pitch motion of rafts and floating modular flap. The motion characteristic, performance and optimization of the ModuleRaft wave energy converter are investigated under regular wave conditions using ANSYS-AQWA. The effect of wave frequency, power take-off (PTO) damping coefficient and floating/fixed main structure on capture factor is analyzed. Results indicate that using a single point mooring (SPM) system, the ModuleRaft WEC can operate optimally by utilizing all directions wave energy. In addition, comparing WEC with and without rafts, it was found that the capture factor of the modular flap with rafts is much better than the conventional floating modular flap-type WEC. Moreover, the three most influential parameters; wave frequency, PTO damping coefficient and fixed main structure, have a significant effect on the capture factor of the ModuleRaft WEC. Highlights: Hybrid concept of pendulum and raft wave energy converters. Motion characteristic and performance of the ModuleRaft wave energy converter are investigated using ANSYS-AQWA. Wave frequency, damping coefficient and fixed main structure affect capture factor of the wave energy converter.